PELATIHAN PENJERNIHAN LIMBAH RUMAH TANGGA MINYAK JELANTAH DENGAN MENGGUNAKAN EKSTRAK KULIT PISANG DI DAERAH LAGOA, JAKARTA UTARA - Fadliah; Rangga Wastu, Apriandi Rizkina; Yasmaniar, Ghanima; Husla, Ridha (Universitas Trisakti, 2023)
Used cooking oil is the oil that is used repeatedly and its structure has changed due to changes in color, smell, and the physical and chemical properties of the cooking oil itself. The use of used cooking oil can irritate the throat, itchy throat, damage health, cause cancer, and can reduce intelligence. To reduce toxins in the used cooking oil can be done in various ways, one of which is by using banana peels. In general, people use bananas for direct consumption or processing as food ingredients. However, banana peels are immediately thrown away and only become waste. This is very unfortunate because people do not know about the benefits of banana peels. Banana peel is absorbent meaning it absorbs other substances on its surface without a chemical reaction. The purpose of this activity is to train the community to be able to utilize waste banana peels and process them to purify household waste cooking oil. So that the community can help reduce organic material waste and minimize the disposal of these two wastes by implementing a zero waste industry.